Grau de risco do pé diabético na atenção primária à saúde - Silva, Patricia Simon da (2020)
Objective: to investigate the risk classification for diabetic foot and associated factors in individuals with diabetes mellitus. Method: a cross-sectional study among users followed up in a basic health unit. Data were collected with patients who underwent the nursing consultation through a clinical evaluation form of lower limbs. The analysis was conducted by means of multivariate logistic regression. Results: total of 69 participants evaluated, 52.8% presented some degree of risk. There was a higher chance among men, elderly, with reports of pain at rest in the legs and feet, history of ulcer and/or amputations, with nursing diagnosis of "impaired skin integrity in the elderly". Conclusion: most of the users evaluated do not have a high risk, but the focus should be on self-care for the prevention of such injury and the clinical examination of lower limbs by nurse.